Specialized Pre-Training of Neural Networks on Synthetic Data for Improving Paraphrase Generation - Skurzhanskyi, O. H.; Marchenko, O. O.; Anisimov, A. V. (Cybernetics and systems analysis, 2024)
Paraphrase generation is a fundamental problem in natural language processing. Due to the significant success of transfer learning, the “pre-training → fine-tuning” approach has become the standard. However, popular general pre-training methods typically require extensive datasets and great computational resources, and the available pre-trained models are limited by fixed architecture and size. The authors have proposed a simple and efficient approach to pre-training specifically for paraphrase generation, which noticeably improves the quality of paraphrase generation and ensures substantial enhancement of general-purpose models. They have used existing public data and new data generated by large language models. The authors have investigated how this pre-training procedure impacts neural networks of various architectures and demonstrated its efficiency across all architectures.